THE USE OF CODE-MIXING PERFORMED BY EFL STUDENT TEACHERS AND LECTURERS AT STAIN KERINCI: A QUALITATIVE STUDY - Urip Sulistiyo; Reko Hary Putra (Universitas Jambi, 2019)
This research reviews the use of code-mixing performed by students and lecturers in STAIN Kerinci, Jambi. Using qualitative approach, with some observations and interviews as the data collection technique, the researchers explore students and lecturers’ motivations in demonstrating code-mixing. The researchers also gather their perceptions toward the employment of code-mixing in speaking subject. It is found that there are some problems that make the students and lecturers turn to code-mixing during learning process. In fact, it because such phenomenon eases the learning process itself. Based on the discussion and conclusion, although code-mixing has positive impacts on the participants, the researcher suggested that the lecturer should use English frequently and keep controling and motivating the students to acquire English more.